The twins bargain - Carter, Lisa (Lisa Cox), 1964- (Love inspired., 2019)
"Nursing student Amber Fleming couldn't be more stunned when ex-marine Ethan Green makes an offer: he'll babysit her twin girls if she cares for his injured grandmother. Amber knows it's temporary. Ethan isn't one for roots- or their hometown. But his steadfast caring has her wanting more than friendship. And with help from Amber's mischievous twins, can they risk becoming a forever family?"--Back cover.